2004
DOI: 10.1051/0004-6361:20041388
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of multiple shells around V838 Monocerotis

Abstract: Abstract. We report the discovery of multiple shells around the eruptive variable star V838 Mon. Two dust shells are seen in IRAS and MSX images, which themselves are situated in a shell of CO. This securely establishes V838 Mon as an evolved object. We revisit the light echo, which arises from scattering off the innermost resolved dust shell, to infer a distance to V838 Mon of > ∼ 5.5 kpc. The dynamical timescales of the ejected shells, location in the Milky Way and inferred luminosity are consistent with V83… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 13 publications
2
30
0
Order By: Relevance
“…3.2. The emission that van Loon et al (2004) plotted as the upper-left section of their CO loop comes from the survey of Dame et al (1987) and is way down in the noise of this survey.…”
Section: Discussion and Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…3.2. The emission that van Loon et al (2004) plotted as the upper-left section of their CO loop comes from the survey of Dame et al (1987) and is way down in the noise of this survey.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…van Loon et al (2004) argue that there are multiple shells around V838 Mon, which were ejected by V838 Mon in previous eruptions. Hence they reason that prior to eruption V838 Mon was an asymptotic giant branch (AGB) star.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(However there is no direct evidence that both components form a real binary.) The system is embedded in the interstellar medium, which is most likely to be related to molecular clouds seen around the position of V838 Mon, rather than to be expelled by the object itself as argued by van Loon et al (2004).…”
Section: Introductionmentioning
confidence: 98%
“…Another possibility is the merger of a pair of mainsequence binary stars (Soker & Tylenda 2003). It has also been suggested that V838 Mon is a post-asymptotic giant branch (AGB) star and the event was due to He flash (van Loon et al 2004). Finally, Retter & Marom (2003) have suggested that the eruption was due to the accretion of several close-in giant planets by an expanding giant or AGB star.…”
Section: Introductionmentioning
confidence: 99%